2013
DOI: 10.1371/journal.pone.0068506
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Selective Hyperthermia Induced by Short-Wave Capacitively-Coupled RF Electric-Fields

Abstract: There is a renewed interest in developing high-intensity short wave capacitively-coupled radiofrequency (RF) electric-fields for nanoparticle-mediated tumor-targeted hyperthermia. However, the direct thermal effects of such high-intensity electric-fields (13.56 MHZ, 600 W) on normal and tumor tissues are not completely understood. In this study, we investigate the heating behavior and dielectric properties of normal mouse tissues and orthotopically-implanted human hepatocellular and pancreatic carcinoma xenogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 22 publications
0
50
1
Order By: Relevance
“…has a unique, frequency-dependent permittivity that describes how it will store and convert electrical energy into heat. We have recently shown that pancreatic and hepatic tumors have larger permittivity loss-tangents than normal, healthy tissues, meaning they will absorb more RF energy, as well as dissipate more RF energy into heat (9). We also anticipate that A. fumigatus (Af293) has an RF-sensitive permittivity, given that hyphal damage was so severe for such a short space of RF exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…has a unique, frequency-dependent permittivity that describes how it will store and convert electrical energy into heat. We have recently shown that pancreatic and hepatic tumors have larger permittivity loss-tangents than normal, healthy tissues, meaning they will absorb more RF energy, as well as dissipate more RF energy into heat (9). We also anticipate that A. fumigatus (Af293) has an RF-sensitive permittivity, given that hyphal damage was so severe for such a short space of RF exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…Further, cancerous cells in general seem to have higher ionization, thus are more susceptible to electromagnetic heating. It could be shown that an increased energy deposition occurred in a pancreatic tumor tissue compared to a normal pancreatic tissue [18]. Thus there exists a higher selectivity of tumor cells to the heating effect.…”
Section: Adding Hyperthermia As An Adjuvant Treatment Option In Pancrmentioning
confidence: 99%
“…responsible for the peak heating behavior observed for aqueous salt solutions, 2,3 which occurs when e 00 r % e 0 r . 6 For water, the value of e 0 r at 13.56 MHz is 78.5, so peak heating occurs when e 00 r is also 78.5, which corresponds to a conductivity of 0.06 S/ m. Conductivity or e 00 r can be increased with minimal changes in e 0 r by addition of electrolytes. Propylene glycol (PG), ethanol, and glycine betaine (GB) were each mixed with water in various ratios to produce semi-aqueous systems with a variety of dielectric properties.…”
mentioning
confidence: 98%
“…Such an understanding may have direct applications in non-invasive RF cancer hyperthermia therapy. [4][5][6][7][8][9] Although most tissues in the human body are made up primarily of water and other tissues, such as fat and bone, have drastically different dielectric properties and are expected to behave differently. Overheating of the subcutaneous fat layer, for example, is a major limiting factor in hyperthermia cancer therapy (especially at 13.56 MHz) and must be overcome if this technology is to be safely implemented in the clinic.…”
mentioning
confidence: 99%
See 1 more Smart Citation